2014
DOI: 10.2215/cjn.09810913
|View full text |Cite
|
Sign up to set email alerts
|

Association of Walking with Survival and RRT Among Patients with CKD Stages 3–5

Abstract: Background and objectives Patients with CKD can benefit from an increase in physical activity. Walking is one of the most common exercises in patients with CKD; however, the association of walking with outcomes in patients with CKD is not clear. This study investigated the association of walking with overall mortality and RRT in patients with CKD stages 3-5.Design, setting, participants, & measurements All patients with CKD stages 3-5 in the CKD program of China Medical University Hospital from June 2003 to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 32 publications
4
56
1
5
Order By: Relevance
“…Previous research has shown that exercise during HD did not cause adverse events 11) and even prevented new cardiovascular events. 12) Exercise has been reported to improve dialysis efficiency, 13) but the results of this study showed no such effect. Possible reasons for this are that the subjects of the present study were dialysis patients who resided at home, meaning that they were in a stable environment.…”
Section: Discussioncontrasting
confidence: 66%
“…Previous research has shown that exercise during HD did not cause adverse events 11) and even prevented new cardiovascular events. 12) Exercise has been reported to improve dialysis efficiency, 13) but the results of this study showed no such effect. Possible reasons for this are that the subjects of the present study were dialysis patients who resided at home, meaning that they were in a stable environment.…”
Section: Discussioncontrasting
confidence: 66%
“…29 Achieving higher levels of ambulation, or at least slowing or preventing decline in gait speed, may enable a person to more safely negotiate household and community environments. 30 The Renal Exercise Demonstration Project found that patients undergoing HD who participated in an exercise intervention had a mean change in gait speed of 0.09 ±0.15 m/s, while gait speed change in the control group who received no intervention was -0.04 ± 0.16 m/s (p =0.02), 8 providing evidence that gait speed could be improved with counseling and encouragement for increased physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Only four of them are recruiting patients. In addition, MDC had been extensively used in Taiwan since 2003 [36] and other countries. The lower all-cause mortality associated with MDC was mainly observed in studies that take allcause mortality after starting dialysis into consideration [11,12,14,22,23,25].…”
Section: Discussionmentioning
confidence: 99%